Bilateral Ureteric Ligation - Affram, R.K. (Ghana Medical Journal, 2008)
About a decade ago a publication on renal failure due to bilateral ureteric ligation during gynaecological operation seen at the Dialysis Unit of the Korle Bu Teaching Hospital in Accra was published in the International Journal of Gynaecology and Obstetrics. This is a specialist journal which the doctor at the Regional and District Hospital level in Ghana may not have access to. In this issue of the journal is a paper which brings to the fore the same problem of bilateral tubal ligation during gynaecological surgery as described earlier. This complication of pelvic surgery will now be known by all doctors who read this journal and hence forth will recognize this complication early.
Journal Article
Keywords: gynaecological operation; Dialysis; Ureteric; Ligation